Fontina Gen. nov. (Bacillariophyta): a new diatom genus from a thermo-mineral spring of the French Massif Central (France). Issue 1 (2nd January 2022) - Beauger, Aude; Wetzel, Carlos E.; Voldoire, Olivier; Allain, Elisabeth; Breton, Vincent; Miallier, Didier; Ector, Luc
Abstract : Light and scanning electron microscope observations on the genus Fontina gen. nov. from a thermo-mineral spring of the Massif Central (France) are presented. Based on morphology, the new genus shows features that have not been described previously, such as the stria pattern, interrupted at the valve face/mantle junction and composed of one long, slit-like areola on both valve face and mantle. Externally, areolae are closed by hymenes. Fontina arverna sp. nov. is described as the typus generis of Fontina . This new genus was compared with some similar freshwater genera such as Adlafia, Chamaepinnularia, Genkalia, Germainiella, Microfissurata and Nupela . So far, we are unable to establish an evolutionary link or cladistic association with currently known genera. The new genus is described from a sampling site characterized by high conductivity and high carbonate concentration, brackish conditions and whose water originates deep in the crust (high lithium concentration).